LIPOPOLYSACHARIDE GENE BASED DEVELOPMENT AND OPTIMIZATION OF DIAGNOSTICS FOR FRANCISELLA TULARENSIS - J. Muhammad; M. Rabbani; K. Muhammad; M. Wasim; K. Dewan; A. A. Anjum; A. A. Sheikh; A. Ahmad; F. Akhtar; M. Nisar; B. M. Jayarao; G. S Kirimanjeswara6. (Journal of Animal and Plant Sciences, 2017)
Francisella tularensis (FT) is a Tier 1 select agent due to its low infectious dose and potential threat of being a bio-weapon while causing zoonotic disease in more than 150 mammalian species. Since there are concerns in its culturing at bio-containment deficient labs in developing countries and its subsequent diagnostics and surveillance accordingly, here we proposed a conventional PCR based test of choice that have been developed and optimized for detection of FT using tul4 gene specific primers. Annealing temperature and genomic DNA concentration was optimized using a live vaccine strain. Specificity of primer showed FT detection in soil DNA in the presence of other cross-reactive organism. Sensitivity was determined in two fold dilutions with detection limit of up to 320 pg/µL. Utilizing pET28a vector, a construct was prepared containing transformed tul4 gene (450bp) showing 100% sequence homology to query gene sequence. These results suggest tul4 gene based constructs in vector could be shared to developing countries while developing diagnostic assays as positive control and could potentially be used for lipoprotein purification for ELISA kit development.
Keywords: tul4 gene; primer; conventional PCR; specificity; sensitivity; transformation